Gender differences in responsiveness to a homo economicus prime in the gift-exchange game - Vanessa Mertins; Susanne Warning (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2013)
It has recently been claimed that women's social preferences are easier to manipulate than men's. We tested for gender differences in responsiveness to a homo economicus prime in a gift-exchange experiment with 113 participants. We observed gender differences in the direction of prime-to-behavior effects. For men, we found that primed participants behaved more selfishly than non-primed men as expected. However and surprisingly, for women we observed that participants primed toward selfishness behaved less selfishly than non-primed women. To explain this counterintuitive result, we suggest that prime-to-behavior effects are sensitive to individuals' associations with the prime. We surveyed 452 students to test whether the homo economicus prime activated systematically different associations among men and women. We found strong evidence that women have significantly less positive associations with the homo economicus concept than men, pointing to a likely reason for the observed contrast effect among women.
Keywords: C91; D03; D63; M52; 330; priming; gender difference; gift exchange; experiment